2017
DOI: 10.3390/v9080213
|View full text |Cite
|
Sign up to set email alerts
|

Can Antiretroviral Drugs Be Used to Treat Porcine Endogenous Retrovirus (PERV) Infection after Xenotransplantation?

Abstract: Porcine endogenous retroviruses (PERVs) are integrated in the genome of all pigs; they are released as infectious particles, and under certain conditions they can infect human cells. Therefore, they represent a risk when pigs are used as sources of cells, tissues, or organs for xenotransplantation. Xenotransplantation is under development due to the increasing shortage of human transplants. Whereas most porcine microorganisms which may be able to induce a disease (zoonosis) in the transplant recipient can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…70 PERV is susceptible in vitro to nucleoside and non-nucleoside reverse transcriptase inhibitors in common clinical use. 49,[78][79][80][81][82][83] Theoretical strategies have been developed to prevent PERV transmission including use of PERV-C-negative or low virus producing pigs, vaccination, antiretroviral therapy, RNA interference therapies, and PERV knockout animals using Clustered Regularly Interspaced Short Palindromic Repeats-Caspase9 (CRISPR-Cas9) techniques. 84,85 Using CRISPR-Cas9 to target the polymerase gene of PERV elements, inactivation was achieved of all 62 copies of PERV in the immortalized porcine kidney epithelial cell line PK15, which normally releases high levels of infectious PERV in vitro.…”
Section: P Orcine Endog Enous Re Trovirus (Perv )mentioning
confidence: 99%
See 1 more Smart Citation
“…70 PERV is susceptible in vitro to nucleoside and non-nucleoside reverse transcriptase inhibitors in common clinical use. 49,[78][79][80][81][82][83] Theoretical strategies have been developed to prevent PERV transmission including use of PERV-C-negative or low virus producing pigs, vaccination, antiretroviral therapy, RNA interference therapies, and PERV knockout animals using Clustered Regularly Interspaced Short Palindromic Repeats-Caspase9 (CRISPR-Cas9) techniques. 84,85 Using CRISPR-Cas9 to target the polymerase gene of PERV elements, inactivation was achieved of all 62 copies of PERV in the immortalized porcine kidney epithelial cell line PK15, which normally releases high levels of infectious PERV in vitro.…”
Section: P Orcine Endog Enous Re Trovirus (Perv )mentioning
confidence: 99%
“…To date, all preclinical and clinical xenotransplantation studies using pig cells, tissues, and organs have failed to demonstrate transmission of PERV to humans including transplantation of porcine pancreatic islets and over 200 individuals exposed to pig cells or tissues or ex vivo perfusion of pig organs or pig cell-based bioreactors 64,65. If human infection should occur, PERV is susceptible in vitro to nucleoside and non-nucleoside reverse transcriptase inhibitors in common clinical use 49,[78][79][80][81][82][83]. In one early study, persistent microchimerism was observed in 23 patients for up to 8.5 years after treatment without PERV transmission 77.…”
mentioning
confidence: 99%
“…PERV receptors have been identified on human cells and productive infection demonstrated in vitro in certain permissive human target cells . PERV is susceptible to antiretroviral agents in vitro . Any enhancement of retroviral replication due to herpesviral coinfection might alter strategies for infectious disease surveillance or immunosuppressive regimens in xenograft recipients.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] PERV is susceptible to antiretroviral agents in vitro. 32,33 Any enhancement of retroviral replication due to herpesviral coinfection might alter strategies for infectious disease surveillance or immunosuppressive regimens in xenograft recipients. We examined a series of xenografts derived from baboon recipients of porcine GalT-KO renal xenotransplants in vivo to determine whether evidence exists of an interaction between PERV and PCMV within xenograft kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…11,[22][23][24][25] In addition, in the event of detection, PERV is susceptible to anti-virals. 26 Given the current status of xenotransplantation, the risk of transmission appears to be low and not greater than that seen for allotransplantation: pre-clinical screening would reduce the risk further suggesting we may have already met the stringency criteria for "first-in-man" studies. In fact, this is a misnomer as we already have seen clinical trials utilizing pig tissues.…”
mentioning
confidence: 99%